The Effects of Unemployment, Poverty, Education, and Income Disparity on Crime Rate in West Sumatra - Mhd. Daffa Alzahri; Wildan Syafitri (Journal of Development Economic and Social Studies, 2025)
The number of crimes in West Sumatra Province increased drastically in 2023, reaching 12,936 incidents. From 2018 to 2023, the number of crimes in the Province has increased. The Province has been supported by reduced unemployment, poverty, income disparity, and increased education. So, this research was conducted to know the effect of unemployment, poverty, education, and income disparity on crime in West Sumatra Province. The research method used is the panel data regression analysis method with combined data, namely 12 districts and seven cities from 2018 to 2023, which is secondary data collected from Badan Pusat Statistik of West Sumatra Province. The results show that unemployment, poverty, and education positively and significantly affect crime. However, income disparity has no significant effect on crime. Meanwhile, simultaneously, unemployment, poverty, education, and income disparity have a significant effect on crime.